Functional activities and applications of Pequi Oil: a systematic review and meta-analysis - Figueiredo, Stella de Alencar; Dr. Leilson Rocha Bezerra; Souza, Marthyna Pessoa de; Silva Filho , Edson Cavalcanti da; Oliveira , Kataryne Árabe Rimá de; Oliveira Filho , Abrahão Alves de; Leandro da Silva, André; Medeiros, Rosália Severo de; Oliveira , Juliana Paula Felipe de (Food Science and Technology, 2025)
Pequi oil is a promising raw material known for its high content of unsaturated fatty acids, polyphenols, and carotenoids. This systematic review focuses on its potential and industrial applications. A total of 27 studies were selected, and 14 were meta-analyzed. The results demonstrated the oil’s potential in the food industry, where natural antioxidants served as preservatives, stabilizers, and additives, thereby extending the shelf life of products like yogurt and cheese. Additionally, pequi oil has applications in pharmaceuticals, phyto-cosmetics, as well as in nano-emulsions and nanocomposites. The meta-analysis revealed a total effect size of 0.73 with a 95% confidence interval of 0.67–0.79 and a significant p-value (p < .01). Heterogeneity was observed (I2 = 95%; p < .0011), supporting the practical application of pequi oil in various therapeutic interventions. These include antioxidant, anti-inflammatory, antigenotoxic, and anticarcinogenic effects, as well as potential treatments for diseases related to oxidative stress, glycemic control, anemia, reduction of low-density lipoproteins cholesterol, osteoarthritis symptoms, and dermal wound healing. Pequi oil shows considerable potential for product development across various industrial sectors. However, it is essential to explore alternative methods of its exploitation to expand its practical applications and foster new product development.